MITIGATING THE NEGATIVE PSYCHOSOCIAL EFFECTS OF TIKTOK ON ADOLESCENTS THROUGH THE NGAJI SOROGAN AND LAILATUL IJTIMA PROGRAMS: EVIDENCE FROM THE TARBIYATUL MUBTADIIN FOUNDATION, TEGAL REGENCY, INDONESIA - Muhammad Jalaludin (PT. Cadas Insan Madani, 2026)
The rapid expansion of TikTok has significantly influenced adolescents' psychosocial development, affecting their emotional well-being, social interactions, academic engagement, and religious values. Excessive exposure to short-form digital content has been associated with addictive behaviors, reduced interpersonal communication, emotional instability, and declining participation in religious and educational activities. This study aims to analyze the implementation of the Ngaji Sorogan and Lailatul Ijtima programs as community-based Islamic educational strategies to mitigate the negative psychosocial effects of TikTok among adolescents at the Tarbiyatul Mubtadiin Foundation in Gantungan Village, Jatinegara District, Tegal Regency, Indonesia. Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis involving foundation leaders, religious teachers (ustadz), parents, and adolescent participants. The data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, while credibility was ensured through source and method triangulation. The findings reveal that the Ngaji Sorogan program strengthens adolescents' religious literacy, self-discipline, and personal accountability through individualized Qur'anic learning and direct teacher guidance. Meanwhile, the Lailatul Ijtima program fosters social cohesion, emotional resilience, spiritual awareness, and positive peer interaction through collective religious gatherings, discussions, and worship activities. The integration of both programs effectively reduces excessive TikTok use by encouraging productive time management, strengthening self-control, enhancing face-to-face communication, and reinforcing Islamic moral values. The study concludes that traditional Islamic educational programs remain highly relevant as culturally responsive interventions for addressing the psychosocial challenges posed by digital media among adolescents. These findings contribute to the growing discourse on integrating religious education with digital well-being initiatives in contemporary Muslim communities.